Choroba zakrzepowo-zatorowa w okresie menopauzalnym - Grzegorz Stachowiak; Tomasz Stetkiewicz (Menopause Review, 2010)
Venous thromboembolism (VTE) is treated shabbily in gynaecology of the menopausal period. Being a seriouscomplication of neoplasms, operative procedures and – at last – menopausal hormone therapy (MHT), it isundoubtedly noteworthy and calls for in-depth knowledge.